Short Communication: Leaf architectural characteristics of Cinnamomum cebuense Kosterm. (Lauraceae) distributed in different geographical locations, taxonomic identification and conservation concerns - Edgardo Lillo; INOCENCIO E. BUOT JR; ARCHIEBALD B. MALAKI; STEVE MICHAEL T. ALCAZAR; RAAMAH ROSALES; JOHN LOU B. DIAZ; BERNARDO R. REDOBLADO; GLORY GRACE G. GEALON (Society for Indonesian Biodiversity, 2020)
Abstract. Lillo EP, Buot IE Jr., Malaki AB, Alcazar SMT, Rosales R, Diaz JLB, Redoblado BR, Gealon GGG. 2019. Short Communication: Leaf architectural characteristics of Cinnamomum cebuense Kosterm. (Lauraceae) distributed in different geographical locations, taxonomic identification and conservation concerns. Biodiversitas 20: 246-251. Populations of Cinnamomum cebuense Kosterm distributed in three geographic locations were examined in the study. The primary aim of the study was to compare the leaf architectural characteristics of Cinnamomum cebuense Kosterm. (Lauraceae) species distributed in three locations. Specimen morphological characters were described using the Leaf Architecture Working Group (LAWG) Manual. Results showed that the species from Nug-as, Alcoy, Cebu was Cinnamomum cebuense because majority of its leaf architectural characteristics and vein categories were similar to those from Tabunan forest. However, the Cinnamomum species from Mount Nacolod, Southern Leyte was slightly different because there are vein categories and other leaf characteristics not similar to those collected from Tabunan forest. The species as one of the endemic plant species on the island of Cebu need to be conserved and protected as they are endangered in the wild.